Microbial diversity across tea varieties and ecological niches: correlating tea polyphenol contents with stress resistance - Yao, Su-hang; Zhou, Chi; Li, Sai-jun; Li, Yu-han; Shen, Cheng-wen; Tao, Yu; Li, Xin (Frontiers in Microbiology, 2024)
Microorganisms exhibit intricate interconnections with tea treesplants; however, despite the well-established role of microorganisms in crop growth and development, research on microbes within the tea plant remains insufficient, particularly regarding endophytic microorganisms. In this study, we collected samples of leaves and rhizosphere soils were collected from 'Zhuyeqi', 'Baojing Huangjincha#1Baojing Huangjinchayihao', 'Anjibaicha'Baiye#1', and 'Jinxuan' varieties planted. Our analyses revealed significant variations in tea polyphenol contents among tea varieties, particularly with the 'Zhuyeqi' variety exhibiting higher levels of tea polyphenols (>20% contents). Microbiome studies have revealed that endophytic microbial community in tea plants exhibited higher host specificity compared to rhizospheric microbial communityrhizosphere microbial community.Analyses of across-ecological niches of the microbial community associated with tea plants of the microbiota associated with tea plants revealed that soil bacteria serve as a significant reservoir for endophytic bacteria in tea plants, Balneola Bacillus may play a crucial role in shaping the bacterial community across-ecological niche within the tea plants with higher tea polyphenol levels. In the aforementioned analyses, the microbial community of 'Zhuyeqi' exhibited a higher degree of host specificity for leaf endophytic microorganisms, the topological structure of the co-occurrence network is also more intricate, harboring a greater number of potential core microorganisms within its nodes. A closer examination was conducted on the microbial communityA more intricate examination was conducted on the microbial community of 'Zhuyeqi', further analyses of its endophytic bacteria indicated that its endophytic microbial community harbored a greater abundance of biomarkers, particularly among bacteria, and the enriched Methylobacterium and Sphingomonas in 'Zhuyeqi' may play distinct roles in disease resistance and drought resilience in tea plants. In summary, this study has shed light on the intricate relationships of tea plant varieties with their associated microbial communities, unveiling the importance of microorganisms and tea varieties with higher tea polyphenols, and offering valuable insights to the study of microorganisms and tea plants.this study shaded light on the intricate relationship between tea plant varieties and their associated microbial community and unveiled the importance of the tea varieties with higher tea polyphenols in microbial studies, offered valuable insights for the studies of microorganism-tea plants.